Pneumonies communautaires graves de l'adulte - Sollet, J.-P. (Emc. Anesthe´sie-Re´animation, 2005)
Community-acquired pneumonias are major causes of hospitalization and death. Immediate assessment of severity, based on accurate clinical criteria, is an important step for rapid intensive care management and control of organ failures. Appropriate microbiological sampling should be performed prior to the antimicrobial therapy that should be initiated promptly after the diagnostic. Despite identification techniques, only 50% of community-acquired pneumonia cases are documented. Antibiotherapy is initially empirical. The goal is to provide optimal therapy for the most commonly identified causes of lethal pneumonia: extracellular and intracellular pathogens. A therapeutic regimen with a β-lactam combined with a macrolide or a fluoroquinolone is recommended. This combination should be always active against pneumococci. Despite increased pneumococcal penicillin resistance, the recent recommendations are not modified. Respiratory fluoroquinolones may be an alternative in case of major increase of pneumococcal resistance to β-lactams. In some special populations, with regard to underlying structural disease of the lung and other risk factors, Pseudomonas aeruginosa must be taken into account. The severity of some community-acquired pneumonias necessitates the use of adjunctive treatments. Reassessment should be undertaken 72 hours after initiation of therapy in order to evaluate the response to treatment, to simplify or to readapt the empirical treatment. Unjustified continuation of wide spectrum antibiotics leads to adverse events and widespread of bacterial resistance. The poor outcome of severe pneumonias justifies research on initial process of care and new therapeutics.